Nilai Kesetiakawanan Sosial Masyarakat Manado sebagai Dasar Penyelenggaraan Kesejahteraan Sosial di Kota Manado - raharjo, tyaseko (Jurnal Penelitian Kesejahteraan Sosial, 2019)
This study aims to describe the value of social solidarity of the people of Manado as the basis for organizing social welfare. The approach used is descriptive qualitative to reveal the value of social solidarity of the people of Manado as a basis for the implementation of good social welfare related to the value of social wisdom. The study was conducted in the city of Manado with the urban community setting, because the city has a uniqueness in community life with the inherent value of local wisdom as a high-tolerance living philosophy. Data sources were determined purposively, namely the Head of the Office of Social Affairs and Community Empowerment of Manado City, village officials, community leaders, and community members. Data were obtained using interview techniques, observation, and subsequent document review. Data were analyzed descriptively with exposure in narrative form. The results of the study show that the solidarity value of the people of Manado can be used as a basis for the implementation of social welfare which is derived from the value of social wisdom. Torang values all together provide a sense of brotherhood to always establish harmony in society. Sitou Timou Tou gives social services to the community with mutual respect, care, help to help neighbors. Mapalaus provides social services by collaborating and collaborating to alleviate social problems in the community. It is recommended that the Head of the Office of Social and Community Empowerment of Manado City can provide guidance to the social cultural organizations concerned with Manado. Guidance for pillars of social and family welfare workers to keep preserving the value of social solidarity of the people of Manado. Â  Keywords: Social Solidarity Value, Local Wisdom, Manado Community.